Retrospective comparative study on artificial reproductive technology outcomes in women undergoing in vitro fertilization with recombinant gonadotropins - M. A. Kurtser; G. V. Kasyanova; M. M. Ovchinnikova; D. T. Khetagurova (IRBIS LLC, 2022)
Introduction. Currently, various hormonal preparations are used in assisted reproductive technology (ART) programs which allow to profoundly improve protocols for stimulating superovulation.Aim: to comparatively analyze effectiveness of recombinant follicle-stimulating hormone preparations in in vitro fertilization (IVF) and embryo transfer (ET) programs.Materials and Methods. In order to evaluate the effectiveness of gonadotropic drugs, a retrospective analysis of 75 outpatient medical records after routine infertility treatment with IVF and ET programs using follitropin alfa (Gonal-F®), follitropin beta (Puregon®), biosimilar follitropin alfa (Primapur®) for ovarian stimulation was performed. Women examined were divided evenly into groups of 25 patients receiving each drug. The main efficiency indicators of IVF and PE cycles were as follows: the number of aspirated oocytes, the number of embryos obtained, the percentage of clinical pregnancy, as well as «Take Home Baby» parameter.Results. The patients were comparable in age, hormonal status, major parameters of somatic and gynecological history, parity, and infertility factors. The maximum and minimum number of embryos on day 5, including "high quality" embryos was observed in the Primapur® group (4.24 ± 0.52), and the Puregon® group (2.76 ± 0.37), respectively. In the group of patients using Primapur®, the incidence of clinical pregnancy was 44.0 %, in the group using Gonal-f® - 48.0 %, and in the group using Puregon® - 44.0 %, that did not significant differed between groups (p > 0.05). While assessing the frequency of live births, no significant inter-group differences were found. «Take Home Baby» parameter was 52.0 % in the Gonal-f® group, 60.0 % in the Puregon® group (p > 0.05) that was insignificantly higher in the group of patients treated with biosimilar follitropin alfa (64.0 % ).Conclusion. The new drug being a biosimilar follitropin alfa does not differ in clinical efficiency from other gonadotropins and can be used for controlled superovulation induction in ART programs.